Investigation of the Effectiveness of the Program for Coping with Negative Perfectionism - Kara, Ahmet; Eryilmaz, Ali (ISRES Publishing, 2022)
The purpose of this research is to test the effectiveness of the program for dealing with negative perfectionism. For this purpose, a quasi-experimental design was chosen with pre- and post-test measurements in both experimental and control groups. In the quasi-experimental design, pre-test is applied to both experimental and control groups before the experimental process. Then the experimental group is included in the experimental process. No experimental procedure is applied to the control group. Finally, a post-test is applied to both the experimental group and the control group as a result of the experimental process. As a result, the effectiveness of this experimental procedure is tested. There are 14 participants in the study group, who attend a public university's faculty of education at various grade levels and who are between the ages of 19 and 22 (X = 20.85, Ss = 1.09). The data are obtained from the Multi-dimensional Perfectionism Scale. Data were analyzed using nonparametric statistical techniques Wilcoxon Signed Ranks Test and Mann Whitney U test. The evaluation of the effectiveness of the program revealed that while the levels of perfectionism were reduced towards self-oriented and other-oriented from the dimensions of perfectionism; however, the program had no effect on social-oriented perfectionism.
Keywords: Özel Eğitim ve Engelli Eğitimi; Multi-dimensional perfectionism; Negative perfectionism; Perfectionism program.; Special Education and Disabled Education; 4. Education; 3. Good health